Integrating YouTube into EAP Pedagogy to Foster Students’ Academic Speaking Competence in EFL Classrooms - Ida Maulida (AL-ISHLAH: Jurnal Pendidikan, 2026)
The increasing demand for English for Academic Purposes (EAP) proficiency requires EFL learners to develop advanced academic speaking skills. However, limited exposure to authentic academic discourse remains a major challenge. Digital platforms such as YouTube may provide multimodal input to support speaking development.This study examines whether integrating YouTube into EAP pedagogy improves students’ academic speaking competence.  A quasi-experimental pre-test–post-test non-equivalent control group design was used with N = 14 university EFL students (n = 7 per group) over 8 sessions (one semester). Data were collected through CEFR-based speaking tests, audio/video recordings, and rater scores, with an additional Likert-scale questionnaire for the experimental group. Quantitative data were analyzed using paired- and independent-samples t-tests, and N-gain scores; qualitative support came from learner perception data.Both groups improved significantly; however, the experimental group showed larger gains (M_pre = 61.14, SD = 2.41; M_post = 81.57, SD = 2.64) than the control group (M_pre = 61.00, SD = 2.16; M_post = 68.57, SD = 1.72). Paired t-tests indicated significant improvement in the experimental group, t(6) = −55.38, p .001, with a large effect. N-gain scores were moderate for the experimental group (52.75%) and low for the control group (19.41%). Questionnaire results indicated positive perceptions (M ≈ 4.43–4.71).Findings suggest that YouTube integration may enhance academic speaking through authentic input and multimodal learning. Pedagogically, structured video-based tasks are recommended in EAP instruction. However, results should be interpreted cautiously due to the small sample size and non-random assignment.